Variations of Performance and Pressure Pulsation During Cavitation in Centrifugal Pumps with Entrained Air - Deng Fanjie (EDP Sciences, 2021)
Most of the research on the cavitation with entrained air has focused on the military direction, but it ,about centrifugal pumps, which is relevant to people's livelihood, is still relatively lacking. In order to study the basic law of the development of cavitation inside centrifugal pumps under aeration conditions, a test bench suitable for cavitation experiments with incoming flow containing gas was obtained. Furthermore, a single-stage single-suction 6-blade centrifugal pump was used as the research object to conduct pressure pulsation experiments under cavitation condition when the incoming flow was 1.0% air viod fraction at 2900r/min-50m3/h. The results showed that: After cavitation happened, the greater aeration content will deteriorate the pump's anti-cavitation performance, but the head curve is more gentle in falling down compared to natural cavitation. Hence aeration has a beneficial effect on the performance degradation of the pump under the cavitation condition. At the same time, before the cavitation number drops to the fracture cavitation number of the pump, aeration has improvement in the efficiency of the pump in different degrees , especially in the situation with the ventilated rate of 1.0%. The main frequency of pressure pulsation at the inlet and outlet of the test pump after aeration is dominated by the blade frequency. The shaft frequency signal at the outlet gradually decreases with the cavitation number lessened. Moreover the amplitude of the blade frequency grows slightly with the reduction of the cavitation number. But it tends to soar when the cavitation number is less than the fracture cavitation number.